2021
DOI: 10.7753/ijsea1001.1001
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Thaw Resistance of Fine-Grained Soils Stabilized with Waste Material Mixtures

Abstract: This paper evaluates the use of waste material mixtures including marble dust and scrap tire rubber the stabilization of fine-grained soils in order to remove the effects of freeze-thaw cycles. In this study, a fine-grained soil material was stabilized by using waste material mixtures. Natural and stabilized fine-grained soil samples were subjected to freeze-thaw cycles under different curing periods. After the freeze-thaw cycles, compressive strength tests were performed to investigate effects of waste materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In Turkey, research carried out on the application of pine sawdust powder passing the No. 4 sieve in Erzurum region soil showed a decrease in the MDD and an increase in the OMC and strength of unconfined compression with the increase in the percentage of sawdust added [1,108,109]; additionally, research carried out adding 1 to 5% of sawdust powder passing No. 20 sieve in Istanbul fine soil showed the strength to unconfined compression increased with the increase in the percentage of sawdust added, showing optima of 3% and 2% respectively, permeability also increased with the increase in the percentage of sawdust added, while the PI, MDD, and OMC decreased.…”
Section: Sawdust Powdermentioning
confidence: 96%
See 1 more Smart Citation
“…In Turkey, research carried out on the application of pine sawdust powder passing the No. 4 sieve in Erzurum region soil showed a decrease in the MDD and an increase in the OMC and strength of unconfined compression with the increase in the percentage of sawdust added [1,108,109]; additionally, research carried out adding 1 to 5% of sawdust powder passing No. 20 sieve in Istanbul fine soil showed the strength to unconfined compression increased with the increase in the percentage of sawdust added, showing optima of 3% and 2% respectively, permeability also increased with the increase in the percentage of sawdust added, while the PI, MDD, and OMC decreased.…”
Section: Sawdust Powdermentioning
confidence: 96%
“…200). Regarding the investigations that used powder sawdust [1,8,36,48,72,95,[108][109][110], it was observed that these were screened with sieves of openings between 4.75mm and 0.42mm (Sieve No. 4 and Sieve No.…”
Section: Fiber Length and Sizementioning
confidence: 99%
“…Several studies have investigated waste marble powder as a stabilizer for fine-grained soils. These studies have generally found that marble powder can effectively strengthen clayey subgrade and increase its bearing capacity for traffic loads [ 1 , 5 , 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For example, Sivrikaya et al investigated the efficiency of marble powder in stabilizing fine-grained soils regarding volume change.…”
Section: Introductionmentioning
confidence: 99%
“…In the modification of clay soils, waste/residue materials and natural rocks or minerals are widely used today as additives, both because they can reduce environmental pollution by reducing carbon dioxide emissions, which is a global problem, during production, and because they are economical and environmentally friendly [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%